Instruments, Investor Base, and Recent Developments in the Malaysian Government Bond Market - Lu, Yinqiu; Yakovlev, Dmitry (Washington, D.C. : International Monetary Fund, 2018)
Foreign holdings of Malaysian local currency (LCY) government bonds have increased since the global financial crisis. By exploring the micro-level bank by bank and fund by fund data, we are able to shed light on the key features of the LCY government bonds including their investor base. The data suggest that to gain exposure to the Malaysian credit, holding cash bonds is generally only one part of the strategy of foreign investors and in many cases FX derivatives are involved. The availability of an efficient FX derivatives market could help to attract a wider range of foreign investors and enrich the bond market. Meanwhile, the analysis of the risk related to the foreign ownership ideally could also cover the role of derivatives. The analysis also allows us to conclude that despite the importance of foreign investors, domestic participants, as the core investor base, could help to ensure the stability and proper functioning of the bond market.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet